Solving a taxonomic puzzle: integrative taxonomy reveals new cryptic and polymorphic species of Oscarella in south-eastern Brazil (Homoscleromorpha : Oscarellidae) - Stillitani, Daniele; Ereskovsky, Alexander; Perez, Thierry; Ruiz, Cesar; Laport, Marinella S.; Puccinelli, Gabriela; Hardoim, Cristiane Cassiolato Pires [UNESP]; Willenz, Philippe; Muricy, Guilherme (Csiro Publishing, 2022)
The sponge genus Oscarella is very important for the understanding of the early evolution of Metazoa, but the identification of its species is particularly difficult due to the absence of a skeleton and high polymorphism, leading to an underestimate of its diversity. The discovery of nine distinct morphotypes of Oscarella co-existing in cryptic habitats in south-east Brazil represents a taxonomic puzzle that requires an integrative taxonomic approach for species delimitation. Here we combined genetic (cox-1 and cob genes), morphological, anatomical, cytological, microbiological, reproductive and ecological datasets to delimit and describe three new species of Oscarella, one of which is highly polymorphic. Oscarella aurantia, sp. nov. is orange, microlobate, with metachromatic vacuolar cells, granular cells, and microgranular cells. Oscarella carollineae, sp. nov. is intertidal, cream or red, microlobate, with granulo-vacuolar cells, dense globular cells, and granular cells. Oscarella ruthae, sp. nov. is highly polymorphic, with tubular or papillate lobes; colour violet, pink, purple, red, orange or cream, often with shades of cream or green at the base; abundant clusters of vacuolar cells type 1, and rare vacuolar cells type 2 and microgranular cells. No single character was sufficient for species delimitation due to high intraspecific variation. Integration of multiple datasets was essential to delimit species of Oscarella and would also be helpful for the taxonomy of other polymorphic sponges.
Keywords: Biodiversity; Biology; Brazil; Homosclerophorida; Porifera; Species delimitation; Systematics; Tropical Southwestern Atlantic